Context-Based Teaching in Mathematics Education: Theoretical Foundations and Teaching Models - Roka, Jasbir; Bist, Resham Bahadur; Khanal, Bishnu (Far Western Review, 2025)
The main objective of this paper is to discuss the theoretical foundation of Context Based Teaching (CBT) models. It reviews the philosophical assumptions: cognitive constructivism, social constructivism and realistic mathematics education (RME) and established teaching models: DILA (display, inquiry, learning community, and authentic assessment) model, the 5E instructional model, the CTCA (culturo-techno contextual) model, and the REACT (relating, experiencing, applying, cooperating, and transforming). Through the comprehensive review, it is found that these foundational pedagogical theories and instructional models related to the CBT approach enhance students' motivation, engagement, and conceptual understanding. Among them, the REACT model is effective for contextualizing mathematics teaching in real-life situations. Therefore, this review provides an insight into adopting the REACT model for CBT-based interventions and curriculum reform in diverse settings of mathematics education.